2018
DOI: 10.4103/jehp.jehp_114_17
|View full text |Cite
|
Sign up to set email alerts
|

Sleep hygiene among veterinary medical students

Abstract: OBJECTIVE:The objective of this study was to better understand veterinary medical students’ sleep hygiene and identify the extent to which sleep hygiene behaviors may result in consequences (either positive or negative) for students.SAMPLE:A total of 187 doctor of veterinary medicine (DVM) program students at a large College of Veterinary Medicine in the United States.METHODS:The Epworth Sleep Scale and Daytime Sleepiness Scale were administered to 393 students enrolled in the DVM program.RESULTS:About 55.1% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Veterinary medical education curricula are individually tailored by each institution and no two are identical although there may be similarities. However, these findings combined with those in the previously referenced study do indicate that this is an issue that should be investigated at other institutions (21). Secondly, PSQI and ESS are very general measures of overall sleep health and do not reveal specific objective data about sleep habits and hygiene.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Veterinary medical education curricula are individually tailored by each institution and no two are identical although there may be similarities. However, these findings combined with those in the previously referenced study do indicate that this is an issue that should be investigated at other institutions (21). Secondly, PSQI and ESS are very general measures of overall sleep health and do not reveal specific objective data about sleep habits and hygiene.…”
Section: Discussionsupporting
confidence: 56%
“…However, almost no information is available about the sleep health of veterinary students. The lone available study in this area revealed that >50% of students reported getting less than the recommended amount of sleep as well as having significant daytime sleepiness (21). In that study 28% of students reported having trouble sleeping, 42% rated their sleep quality as fair or poor, and 68% reported driving while drowsy (21).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that girls are more prone to daytime sleepiness; however, this was not the case with all investigations, as some researchers suggest that there are no gender differences in this matter. [ 57 58 59 60 ]…”
Section: Discussionmentioning
confidence: 99%